Total flux of diatoms and relative composition of diatom groups in trap samples at the CBmeso (=Cape Blanc mesotrophic), off Mauritania - Oscar E Romero (PANGAEA, 2020)
This study builds on earlier investigations of multiyear variability of the diatom flux captured with sediment traps deployed at the mesopelagial mooring site CBmeso (= extquotesingleCape Blanc mesotrophic extquotesingle, formerly known as CB). The main goal of this study is the description of the multiyear dynamics of the total diatom flux and the shifts in the species-specific composition of the assemblage at site CBmeso during almost 20 years (March 1988 through June 2009).